2021
DOI: 10.9734/jpri/2021/v33i1731300
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Fine Needle Aspiration and Cytology in Solitary Thyroid Nodule

Abstract: Objective: To determine the efficacy of fine needle aspiration and cytology (FNAC) in the solitary thyroid nodules at tertiary care Hospital. Materials and Methods: This study was conducted in department of general surgery at Liaquat University Hospital Jamshoro/ Hyderabad during one year from June 2015 May 2016. The study included all subjects of any gender and age who had a solitary nodule that was confirmed clinically or through thyroid scan. To achieve a tissue diagnosis before surgery, the study par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…A similar study by Haider et al, in 2021 20 which is very close to our results; 50 patients were included in the study, 28 (56%) of patients had a solitary nodule at the right lobe while 19 (38%) of patients had a left side lobe nodule and 3 (6%) had an isthmic nodule.…”
Section: Examinationsupporting
confidence: 92%
See 2 more Smart Citations
“…A similar study by Haider et al, in 2021 20 which is very close to our results; 50 patients were included in the study, 28 (56%) of patients had a solitary nodule at the right lobe while 19 (38%) of patients had a left side lobe nodule and 3 (6%) had an isthmic nodule.…”
Section: Examinationsupporting
confidence: 92%
“…29 (96.66%) out of 30 patients were presented with a swelling at the front of the neck and 1 (3.33%) patient presented with neck pain besides the swelling. In another study by Haider et al, in 2021, 20 Thyroid swelling was present in all patients, besides thyroid swellings, 8% of the patients had pain and 4% had irritation in their throats. On the other hand, Hassan et al, in 2013 23 reported that there was pain in the nodule in 4% and dysphagia (6%).…”
Section: Clinical Presentationmentioning
confidence: 84%
See 1 more Smart Citation